Calcium salts of fatty acids with varying fatty acid profiles in diets of feedlot-finished Bos indicus bulls: impacts on intake, digestibility, performance, and carcass and meat characteristics. (28th November 2020) - Nascimento, Felipe A; Silva, Naiara C; Prados, Laura F; Pacheco, Rodrigo D L; Johnson, Bradley J; Cappellozza, Bruno I; Resende, Flávio D; Siqueira, Gustavo R
Abstract: We hypothesized that the inclusion of calcium salts of fatty acid (CSFA ) into the diets and the fatty acid (FA ) profile of the supplements would impact performance and meat characteristics of Bos indicus bulls. Hence, the objective was to evaluate the effects of CSFA profiles on intake, body weight (BW ), carcass, and meat characteristics of feedlot-finished B indicus bulls. Fifty-three Nellore bulls [initial BW 315 ± 5.9 kg and 20 ± 2 mo] were used. At the beginning, 6 bulls were randomly chosen and slaughtered for determination of their BW composition, and the remaining 47 bulls were evaluated during a 140-d experimental period. The bulls were placed in individual pens, blocked according to initial BW and randomly allocated to 1 of the 3 following treatments: (1) control diet containing sugarcane bagasse, ground corn, citrus pulp, peanut meal, and mineral–vitamin mix (CON ), (2) CON with the addition of 3.3% of CSFA from soybean oil (CSO ), or (3) CON with the addition of a mixture of 3.3% of CSFA from palm, soybean, and cottonseed oils (CPSCO ). Diets were offered ad libitum and formulated to be isonitrogenous. Bulls supplemented with CSFA had a greater ( P < 0.01) final BW, dry matter intake, average daily gain (ADG ), feed efficiency (FE ), and FA intake vs. CON. Among carcass parameters, CSFA-supplemented bulls had greater ( P < 0.01) carcass ether extract concentration vs. CON bulls. When the CSFA profile was evaluated (CSO vs. CPSCO), CPSCO bulls had a better ( P ≤ 0.03) FE, carcass ADG, and hot carcass weight (HCW ) vs. CSO bulls. The FA intakes differed among CSFA treatments, as the total saturated, palmitic, and oleic FA intakes were greater for CPSCO ( P < 0.01), whereas lower intakes of total unsaturated and polyunsaturated FA ( P < 0.01) were observed for CPSCO vs. CSO. Samples from the Longissimus muscle contained greater palmitoleic ( P = 0.01) and reduced linoleic ( P = 0.02) FA concentrations in CSFA-supplemented bulls vs. CON bulls. In agreement with the FA intakes, CPSCO-supplemented bulls had a greater ( P ≤ 0.05) unsaturated FA concentration vs. CSO in Longissimus muscle. In summary, CSFA supplementation improved the performance of finishing B. indicus bulls vs. CON. Moreover, the inclusion of CSFA from palm, soybean, and cottonseed oil benefited the FE, carcass ADG, and HCW compared with the inclusion of CSFA from soybean oil, demonstrating the potential of specific FA for improving the performance and meat quality of B. indicus bulls.